Degradable modified PS plastic bowl and preparation method thereof
By melting the combination of flame retardant polystumin, PS-Phenyl-lisa, and degradable polyurethane, to prepare degradable modifiers PS plastic bowls, solving poor degradation and mechanical performance of polystyrene in daily necessities The problem of poor flame retardant performance realizes the efficient degradation and excellent performance of the material.
Patent Information
- Application Number
- CN202411631230.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-09-19
- Filing Date
- 2024-11-15
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Polystyrene has problems such as poor degradability, poor mechanical properties and flame retardant properties in the manufacturing of daily necessities.
A degradable modified PS plastic bowl was prepared by melt-blending flame-retardant polylactic acid, PS-phenyl maleic anhydride copolymer and degradable polyurethane, and molding it.
It improves the biodegradability, mechanical performance and flame retardant performance of the modified PS plastic bowl, making it more suitable for degradable daily necessities.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a degradable modified PS plastic bowl and a preparation method thereof. Background Art
[0002] Plastic products represented by polystyrene (PS) are widely used due to their low cost, chemical stability, good ductility and corrosion resistance. However, most plastics are abandoned or landfilled in the natural environment. These plastic products that enter the environment will decompose into smaller plastic particles under physical, chemical and biological effects, and continue to accumulate in sediments, soil and other media. Therefore, they are regarded as a potential persistent organic pollutant. Modifying polystyrene to prepare degradable modified PS plastics has positive practical significance and has attracted widespread attention. In addition, the poor flame retardancy and mechanical properties of polystyrene are also technical problems that need to be solved urgently.
[0003] Patent application CN105255094A discloses a method for preparing a composite recycled PS / ABS / PP cross-linked modified flame-retardant plastic, which comprises mixing waste ABS, PS, PP plastics, modified graphene and related additives such as toughening agents to obtain a premix, and melt-extruding, drawing, cooling, drying and granulating the premix to obtain a composite recycled PS / ABS / PP cross-linked modified flame-retardant plastic; however, the above-mentioned prior art uses graphene as a flame retardant to improve the flame retardant properties of the material, and uses waste nitrile rubber as a toughening agent to improve the mechanical properties of the material. However, as an inorganic material, graphene has poor compatibility with plastics and cannot be evenly distributed. In addition, nitrile rubber degrades slowly, which reduces the degradability of the recycled plastic.
[0004] Patent application CN1147529A discloses a formula and production process of a filled modified reinforced PE / PP / PS composite material, wherein mica is modified with potassium bifluoride, asbestos is modified with a sulfonyl azide silane coupling agent, and calcium carbonate is modified with an aluminate coupling agent. The three modified fillers are then blended with three matrix resins of polyethylene, polypropylene and polystyrene and related additives to prepare a PE / PP / PS composite material with high hardness and high rigidity; however, the composite material prepared with the three matrix resins of polyethylene, polypropylene and polystyrene used in the above content still has the technical problem of poor degradability. Summary of the invention
[0005] The purpose of the present invention is to provide a degradable modified PS plastic bowl and a preparation method thereof, so as to solve the technical problems in the prior art that when polystyrene is used in the manufacture of daily necessities, the degradability is poor and the mechanical properties and flame retardancy of polystyrene are poor.
[0006] The object of the present invention can be achieved by the following technical scheme: A method for preparing a degradable modified PS plastic bowl comprises the following steps: According to weight parts, 10-20 parts of flame-retardant polylactic acid, 100 parts of PS-phenyl maleic anhydride copolymer and 5-10 parts of degradable polyurethane are added into a torque rheometer, melt-blended to obtain a blend; the blend is compression molded in a mold, and cooled under pressure to obtain a degradable modified PS plastic bowl; The method for preparing the flame retardant polylactic acid comprises the following steps: S1, hexachlorocyclotriphosphazene and ethanol are evenly mixed to obtain an ethanol solution of hexachlorocyclotriphosphazene; S2, anhydrous potassium carbonate and ethylenediamine are evenly mixed to obtain a mixed solid-liquid; an ethanol solution of hexachlorocyclotriphosphazene is added dropwise to the mixed solid-liquid at 5-10°C, and after the addition is completed, the temperature is raised to 20°C, and the reaction is continued for 2-3 hours to obtain a reaction liquid; the reaction liquid is heated to 80-90°C, the solvent is removed by reaction, and a solid is obtained; the solid is washed with deionized water and vacuum dried to obtain a solid intermediate A; S3, mixing TAIC and solid intermediate A, and then adding polylactic acid to blend to obtain a blend; adding the blend to a torque rheometer, blending at 190-200° C. for 5-10 minutes to obtain flame-retardant polylactic acid.
[0007] The reaction mechanism of hexachlorocyclotriphosphazene and ethylenediamine is as follows:
[0008] Reaction principle of solid intermediate A and TAIC:
[0009] Hexachlorocyclotriphosphazene has an active phosphorus-chlorine bond, which can react with ethylenediamine to remove hydrogen chloride to obtain a stable phosphate bond, thereby obtaining a solid intermediate A. The solid intermediate A and the amino group of TAIC undergo an addition reaction to form a CN single bond, thereby obtaining a flame-retardant polylactic acid with a certain cross-linking density.
[0010] Furthermore, in step S1, the usage ratio of hexachlorocyclotriphosphazene and ethanol is 35-45 g:200 mL; in step S2, the usage ratio of anhydrous potassium carbonate and ethylenediamine is 10 g:35-50 mL; in step S2, the vacuum drying temperature is 70-80° C. and the vacuum drying time is 30-60 min.
[0011] Furthermore, in step S3, the usage ratio of TAIC, intermediate A and polylactic acid is 5-10g:30-40g:200-300g; the mixing speed is 100r / min, and the mixing time is 5min; the blending speed is 100r / min, and the blending time is 5-10min.
[0012] Further, the preparation method of PS-phenyl maleic anhydride copolymer comprises the following steps: Polystyrene, phenyl maleic anhydride and DMF are mixed evenly, and then an initiator BPO is added, and the temperature is raised to 120-140°C, and the reaction is carried out for 3 hours to obtain a mixed solid-liquid; the mixed solid-liquid is then heated to 155-160°C, and the DMF solvent is distilled off to obtain a solid; the solid is washed with deionized water and then vacuum dried to obtain a PS-phenyl maleic anhydride copolymer.
[0013] The invention uses polystyrene and phenyl maleic anhydride as reactants, uses DMF as solvent, and under the action of an initiator, a copolymerization reaction occurs to obtain a PS-phenyl maleic anhydride copolymer.
[0014] Furthermore, the usage ratio of polystyrene, phenyl maleic anhydride, DMF and initiator BPO is 8-10g:10-15g:100mL:0.3g; the vacuum drying temperature is 70-80°C, and the vacuum drying time is 30min.
[0015] Furthermore, the degradable polyurethane is prepared by the following steps: A1. Mix sorbitol and polyol vegetable oil, raise the temperature to 80-100° C., then add toluene diisocyanate, stir to obtain a mixed solid-liquid; add a catalyst to the mixed solid-liquid, and react at a constant temperature of 80° C. for 3-5 hours to obtain a polymer; A2. Add 10-20 g of a small molecule chain extender to the polymer, stir at a constant temperature of 50-60° C. for 10-20 min to obtain a sample; cast the sample in a polytetrafluoroethylene mold, and cure at 70° C. for 5-7 days to obtain a degradable polyurethane.
[0016] The reaction principle of degradable polyurethane is: Sorbitol and castor oil are used as soft segment chains and are physically blended in a certain mass ratio; -NCO in toluene diisocyanate reacts with -OH groups in sorbitol and castor oil to generate carbamate to form a prepolymer; small molecule diols with active hydrogen are then used as chain extenders to extend the chain with the remaining isocyanate in the reaction to form a polymer, thereby preparing a degradable polyurethane; the chain extender and the prepolymer are then reacted to prepare a cross-linked polyurethane; the incompatibility between the soft and hard segments in the polyurethane and the strong polarity of the polyurethane molecules allow the molecules to interact with each other to form a crystalline region and produce microphase separation, so that it can serve as a mechanical property reinforcement component for the prepared composite material.
[0017] Furthermore, in step A1, the polyol vegetable oil is any one of castor oil, soybean oil or palm oil and a combination thereof, and the catalyst is dibutyltin dilaurate; the dosage ratio of sorbitol, polyol vegetable oil, toluene diisocyanate and catalyst is 18g:5g:80g:0.3-0.5g; the stirring speed is 5-10min and the stirring time is 100r / min; in step A2, the small molecule chain extender is any one of ethylene glycol, 1,3-butanediol, 1,4-butanediol or 1,6-propylene glycol and a combination thereof.
[0018] Furthermore, the temperature of melt blending is 180-200°C, the rotation speed is 50r / min, the melt blending time is 10-20min; the molding time is 8-10min, the molding pressure is 10MPa; and the pressure holding cooling time is 10min.
[0019] As another aspect of the present invention, a method for preparing a degradable modified PS plastic bowl provides a degradable modified PS plastic bowl.
[0020] The present invention has the following beneficial effects: 1. The degradable modified PS plastic bowl prepared by the present invention is obtained by melt blending and compression molding of flame-retardant polylactic acid, PS-phenyl maleic anhydride copolymer and degradable polyurethane; polylactic acid is a degradable thermoplastic polymer, and the polylactic acid after use can be hydrolyzed into lactic acid; polystyrene (PS) itself has poor degradability, and phenyl maleic anhydride and polystyrene are blended. The anhydride group of phenyl maleic anhydride acts as a strong electron-withdrawing group, so it has a positive polarity, and polystyrene gives electrons due to the conjugation effect of the benzene ring, so it has a negative polarity; polystyrene and phenyl maleic anhydride copolymerize to form a positive and negative electrode attraction. Transition state, in this special state, the chemical bonds are easy to break, so the biodegradability of PS-phenyl maleic anhydride copolymer can be accelerated; polyurethane is difficult to degrade in the natural environment, and environmentally friendly sorbitol and castor oil are used as the soft segment chain of the degradable polyurethane, small molecular weight toluene diisocyanate is used as the hard segment chain, and diol is used as a small molecule chain extender, so as to reduce the molecular weight of the degradable polyurethane and improve the degradability of the degradable polyurethane; the above three components are melt-blended and then compression molded to prepare an easily degradable modified PS plastic bowl.
[0021] 2. The polylactic acid, polystyrene and polyurethane used in the present invention are all flammable plastics. In order to improve the flammability of the modified PS plastic bowl, the present invention designs a flame retardant small molecule and polylactic acid for compounding to obtain flame retardant polylactic acid; hexachlorocyclotriphosphazene has high nitrogen and phosphorus elements and is itself an efficient flame retardant small molecule; however, the phosphorus-chlorine bond of hexachlorocyclotriphosphazene is too active and cannot be used as a stable flame retardant small molecule and polylactic acid for compounding; the present invention reacts ethylenediamine and hexachlorocyclotriphosphazene, which not only realizes the halogen-free flame retardant small molecule, but also can further improve the stability of the flame retardant small molecule. Under the high temperature conditions of melt blending, the residual amino group of the flame retardant small molecule can undergo a dehydration reaction with phenyl maleic anhydride and a dehydration reaction with the excess hydroxyl group of the degradable polyurethane, which can improve the complex strength between the three matrix plastics and improve the stability of the prepared modified PS plastic bowl.
[0022] 3. The cross-linking of flame retardant small molecules and cross-linking agents can improve the cross-linking density and molecular weight of flame retardant small molecules, which can not only improve the stability of flame retardant small molecules, but also help improve the mechanical properties of polylactic acid itself; in addition, under the high temperature conditions of melt blending, the carbonyl functional group in the cross-linking agent TAIC can react with the excess hydroxyl groups in polyurethane to increase the cross-linking density between the components, thereby helping to improve the mechanical properties of the modified PS plastic bowl. The molecular structure of polystyrene is asymmetric, showing rigidity and brittleness, and its mechanical properties such as elongation at break are poor; while polylactic acid and polyurethane have excellent mechanical properties, and good mechanical properties such as elongation at break; polystyrene, polylactic acid and polyurethane are melt blended to form a blending system, which can improve the toughness of polystyrene, thereby improving the mechanical properties of the composite material. DETAILED DESCRIPTION
[0023] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Example 1 This embodiment provides a method for preparing a flame retardant polylactic acid, comprising the following steps: S1, 35g of hexachlorocyclotriphosphazene and 200mL of ethanol were mixed evenly to obtain an ethanol solution of hexachlorocyclotriphosphazene. 10g of anhydrous potassium carbonate and 35mL of ethylenediamine were added to a 500mL three-necked flask, and the mixture was shaken to obtain a mixed solid-liquid mixture; a thermometer was connected to one end of the three-necked flask, and a constant pressure dropping funnel was set at the other end, and then the three-necked flask was transferred to a water bath, and all the ethanol solution of hexachlorocyclotriphosphazene was added thereto through a constant pressure dropping funnel at 5°C. After the addition was completed, the temperature was raised to 20°C, and the reaction was continued for 3h to obtain a reaction solution; the reaction solution was heated to 80°C, and the solvent was removed by reaction to obtain a solid; the solid was washed three times with deionized water, and then vacuum dried at 70-80°C for 30-60min to obtain a solid intermediate A.
[0025] S2. 5 g of TAIC and 30 g of solid intermediate A were blended at 100 r / min for 5 min, and then 200 g of polylactic acid was added and blended at 100 r / min for 5 min to obtain a blend; the blend was transferred to a torque rheometer and blended at 190° C. for 5 min to obtain a flame retardant polylactic acid.
[0026] Example 2 This embodiment provides a method for preparing a flame retardant polylactic acid, comprising the following steps: S1, 40g of hexachlorocyclotriphosphazene and 200mL of ethanol were mixed evenly to obtain an ethanol solution of hexachlorocyclotriphosphazene. 10g of anhydrous potassium carbonate and 45mL of ethylenediamine were added to a 500mL three-necked flask, and the mixture was shaken to obtain a mixed solid-liquid mixture; a thermometer was connected to one end of the three-necked flask, and a constant pressure dropping funnel was set at the other end, and then the three-necked flask was transferred to a water bath, and all the ethanol solution of hexachlorocyclotriphosphazene was added thereto through a constant pressure dropping funnel at 8°C. After the addition was completed, the temperature was raised to 20°C, and the reaction was continued for 2.5h to obtain a reaction solution; the reaction solution was heated to 85°C, and the solvent was removed by reaction to obtain a solid; the solid was washed three times with deionized water, and then vacuum dried at 73°C for 50min to obtain a solid intermediate A.
[0027] S2. 8 g of TAIC and 33 g of solid intermediate A were blended at 100 r / min for 5 min, and then 260 g of polylactic acid was added and blended at 100 r / min for 6 min to obtain a blend; the blend was transferred to a torque rheometer and blended at 195° C. for 6 min to obtain a flame retardant polylactic acid.
[0028] Example 3 This embodiment provides a method for preparing a flame retardant polylactic acid, comprising the following steps: S1, 45g of hexachlorocyclotriphosphazene and 200mL of ethanol were mixed evenly to obtain an ethanol solution of hexachlorocyclotriphosphazene. 10g of anhydrous potassium carbonate and 50mL of ethylenediamine were added to a 500mL three-necked flask, and the mixture was shaken to obtain a mixed solid-liquid mixture; a thermometer was connected to one end of the three-necked flask, and a constant pressure dropping funnel was set at the other end, and then the three-necked flask was transferred to a water bath, and all the ethanol solution of hexachlorocyclotriphosphazene was added thereto through a constant pressure dropping funnel at 10°C. After the addition was completed, the temperature was raised to 20°C, and the reaction was continued for 2h to obtain a reaction solution; the reaction solution was heated to 90°C, and the solvent was removed by reaction to obtain a solid; the solid was washed three times with deionized water, and then vacuum dried at 80°C for 60min to obtain a solid intermediate A.
[0029] S2. 10 g of TAIC and 40 g of solid intermediate A were blended at 100 r / min for 5 min, and then 300 g of polylactic acid was added and blended at 100 r / min for 10 min to obtain a blend; the blend was transferred to a torque rheometer and blended at 200° C. for 10 min to obtain a flame retardant polylactic acid.
[0030] Example 4 This embodiment provides a method for preparing a PS-phenyl maleic anhydride copolymer, comprising the following steps: One end of a 250mL three-necked flask was connected to an electric stirrer, one end was connected to a reflux device, and one end was connected to a thermometer. Then 8g of polystyrene, 10g of phenyl maleic anhydride and 100mL of DMF were added and mixed evenly. Then 0.3g of initiator BPO was added to the three-necked flask, and the three-necked flask was transferred to a water bath, heated to 120°C, and reacted for 3h to obtain a mixed solid-liquid mixture. Then the mixed solid-liquid mixture was heated to 155°C, and the DMF solvent was distilled off to obtain a solid. The solid was washed with deionized water and then dried in a vacuum drying oven at 70°C for 30min to obtain a PS-phenyl maleic anhydride copolymer.
[0031] Example 5 This embodiment provides a method for preparing a PS-phenyl maleic anhydride copolymer, comprising the following steps: One end of a 250mL three-necked flask was connected to an electric stirrer, one end was connected to a reflux device, and one end was connected to a thermometer. Then, 9g of polystyrene, 12g of phenyl maleic anhydride, and 100mL of DMF were added and mixed evenly. Then, 0.3g of initiator BPO was added to the three-necked flask, and the three-necked flask was transferred to a water bath, heated to 130°C, and reacted for 3h to obtain a mixed solid-liquid mixture. Then, the mixed solid-liquid mixture was heated to 158°C, and the DMF solvent was distilled off to obtain a solid. The solid was washed with deionized water and then dried in a vacuum drying oven at 6°C for 30min to obtain a PS-phenyl maleic anhydride copolymer.
[0032] Example 6 This embodiment provides a method for preparing a PS-phenyl maleic anhydride copolymer, comprising the following steps: One end of a 250mL three-necked flask was connected to an electric stirrer, one end was connected to a reflux device, and one end was connected to a thermometer. Then 10g of polystyrene, 15g of phenyl maleic anhydride and 100mL of DMF were added and mixed evenly. Then 0.3g of initiator BPO was added to the three-necked flask, and the three-necked flask was transferred to a water bath, heated to 140°C, and reacted for 3h to obtain a mixed solid-liquid mixture. Then the mixed solid-liquid mixture was heated to 160°C, and the DMF solvent was distilled off to obtain a solid. The solid was washed with deionized water and then dried in a vacuum drying oven at 80°C for 30min to obtain a PS-phenyl maleic anhydride copolymer.
[0033] Example 7 This embodiment provides a method for preparing a degradable polyurethane, comprising the following steps: 1. Add 18 g of sorbitol and 5 g of palm oil into a 250 mL three-necked flask with a condensing device; then heat the three-necked flask to 80°C, add 80 g of m-toluene diisocyanate into the three-necked flask, stir at 100 r / min for 5 min to obtain a mixed solid-liquid; add 0.3 g of catalyst dibutyltin dilaurate into the mixed solid-liquid, react at a constant temperature of 80°C for 3 h to obtain a polymer.
[0034] 10 g of ethylene glycol was added to the polymer, and the mixture was stirred at a constant temperature of 50° C. for 10 minutes to obtain a sample; the sample was cast in a polytetrafluoroethylene mold, and cured at 70° C. for 5 days to obtain a degradable polyurethane.
[0035] Example 8 This embodiment provides a method for preparing a degradable polyurethane, comprising the following steps: 1. Add 18 g of sorbitol and 5 g of castor oil into a 250 mL three-necked flask with a condensing device; then heat the three-necked flask to 90° C., add 80 g of o-toluene diisocyanate into the three-necked flask, and stir at 100 r / min for 6 min to obtain a mixed solid-liquid; add 0.4 g of catalyst dibutyltin dilaurate into the mixed solid-liquid, and react at a constant temperature of 80° C. for 3 h to obtain a polymer.
[0036] 2. Add 15 g of 1,3-butanediol to the polymer, stir at a constant temperature of 53° C. for 15 minutes to obtain a sample; cast the sample in a polytetrafluoroethylene mold, and cure it at 70° C. for 5 days to obtain a degradable polyurethane.
[0037] Example 9 This embodiment provides a method for preparing a degradable polyurethane, comprising the following steps: 1. Add 18 g of sorbitol and 5 g of soybean oil into a 250 mL three-necked flask with a condensing device; then heat the three-necked flask to 100°C, add 80 g of p-toluene diisocyanate into the three-necked flask, stir at 100 r / min for 10 min to obtain a mixed solid-liquid; add 0.5 g of catalyst dibutyltin dilaurate into the mixed solid-liquid, react at a constant temperature of 80°C for 5 h to obtain a polymer.
[0038] 2. Add 20 g of 1,6-propylene glycol to the polymer, stir at a constant temperature of 60° C. for 20 minutes to obtain a sample; cast the sample in a polytetrafluoroethylene mold, and cure it at 70° C. for 7 days to obtain a degradable polyurethane.
[0039] Example 10 This embodiment provides a method for preparing a degradable modified PS plastic bowl, comprising the following steps: According to parts by weight, 10 parts of the flame-retardant polylactic acid prepared in Example 1, 100 parts of the PS-phenyl maleic anhydride copolymer prepared in Example 4, and 5 parts of the degradable polyurethane prepared in Example 7 were added to a torque rheometer at a temperature of 200° C., the speed of the torque rheometer was set to 50 r / min, and blended for 10 minutes to obtain a blend; The blend was placed in a mold, the molding pressure was set to 10 MPa, the molding time was 8 min, the molding was performed, the pressure was maintained and cooled for 10 min, and the material was discharged to obtain a degradable modified PS plastic bowl.
[0040] Embodiment 11 This embodiment provides a method for preparing a degradable modified PS plastic bowl, comprising the following steps: According to parts by weight, 10 parts of the flame-retardant polylactic acid prepared in Example 2, 100 parts of the PS-phenyl maleic anhydride copolymer prepared in Example 5, and 5 parts of the degradable polyurethane prepared in Example 8 were added to a torque rheometer at a temperature of 190° C., the speed of the torque rheometer was set to 50 r / min, and blended for 10 minutes to obtain a blend; The blend was placed in a mold, the molding pressure was set to 10 MPa, the molding time was 8 min, the molding was performed, the pressure was maintained and cooled for 10 min, and the material was discharged to obtain a degradable modified PS plastic bowl.
[0041] Example 12 This embodiment provides a method for preparing a degradable modified PS plastic bowl, comprising the following steps: According to parts by weight, 20 parts of the flame-retardant polylactic acid prepared in Example 3, 100 parts of the PS-phenyl maleic anhydride copolymer prepared in Example 6, and 10 parts of the degradable polyurethane prepared in Example 9 were added to a torque rheometer at a temperature of 200° C., the speed of the torque rheometer was set to 50 r / min, and blended for 20 minutes to obtain a blend; The blend was placed in a mold, the molding pressure was set to 10 MPa, the molding time was 10 min, the molding was performed, the pressure was maintained and cooled for 10 min, and the material was discharged to obtain a degradable modified PS plastic bowl.
[0042] Comparative Example 1 The difference between this comparative example and Example 12 is that the flame-retardant polylactic acid is replaced by polylactic acid of the same mass.
[0043] Comparative Example 2 The difference between this comparative example and Example 12 is that the PS-phenyl maleic anhydride copolymer is replaced by polystyrene of the same mass.
[0044] Comparative Example 3 The difference between this comparative example and Example 12 is that TAIC cross-linking is not used when preparing the flame-retardant polylactic acid.
[0045] Performance Test: 1. According to GB / T1040.2-2006, the degradable modified PS plastic bowl prepared in Examples 10-12 was prepared into dumbbell-shaped splines with a thickness of 3.2 mm. The test was performed at room temperature at a speed of 2 mm / min, and the tensile strength and elongation at break of the splines were recorded.
[0046] 2. The degradable modified PS plastic bowl prepared in Examples 10-12 was prepared into a 100×6.5×3.2 mm 3 According to ISO-4589 standard, the limiting oxygen index value of the specimens prepared in Examples 10-12 was evaluated using a JF-3 oxygen index meter.
[0047] 3. According to GB / T1633-2000, the Vicat softening temperature of the degradable modified PS plastic bowl prepared in Examples 10-12 was measured; wherein the load was 10N and the heating rate was 120°C / min.
[0048] 4. Cut the degradable modified PS plastic bowl prepared in Examples 10-12 into 1×1 cm 2 The initial mass of the samples of different sizes was measured by analytical balance in turn, recorded as N0; the samples were then immersed in sterile simulated body fluids, and in vitro degradation was simulated in a biological incubator, with the degradation temperature set at 37°C and the degradation time set at 60 days. The samples were then taken out and the SBF remaining on the surface of the samples was wiped dry with absorbent paper. The sample was weighed and the mass was recorded on an analytical balance, recorded as N1; the degradation rate of the sample was expressed as the mass loss fraction of the sample, degradation rate = (N0-N1 / N0) × 100%, and the specific test results are shown in Table 1: Table 1
[0049] Data Analysis: The degradable modified PS plastic bowls prepared in Examples 10-12 of the present invention all have excellent mechanical properties, as shown by excellent tensile strength values and elongation at break values. The degradable modified PS plastic bowls prepared in Examples 10-12 of the present invention all have excellent flame retardancy and fire resistance, as shown by high LOI and Vicat softening temperature values. In addition, the degradation performance of the degradable modified PS plastic bowls prepared in Examples 10-12 of the present invention is good, which is manifested as excellent degradation rates. However, since the polylactic acid in Comparative Example 1 has not been flame-retardantly modified, the values of LOI and Vicat softening temperature are reduced, the polystyrene in Comparative Example 2 has not been modified with phenyl maleic anhydride, the degradability is significantly reduced, and the mechanical properties are reduced. The flame-retardant polylactic acid in Comparative Example 3 has not been cross-linked with TAIC, and the values of tensile strength and elongation at break are reduced.
[0050] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing a degradable modified PS plastic bowl, characterized in that: The preparation method comprises the following steps: According to weight parts, 10-20 parts of flame-retardant polylactic acid, 100 parts of PS-phenyl maleic anhydride copolymer and 5-10 parts of degradable polyurethane are added into a torque rheometer, melt-blended to obtain a blend; the blend is compression molded in a mold, and cooled under pressure to obtain a degradable modified PS plastic bowl; The method for preparing the flame retardant polylactic acid comprises the following steps: S1, hexachlorocyclotriphosphazene and ethanol are evenly mixed to obtain an ethanol solution of hexachlorocyclotriphosphazene; S2, anhydrous potassium carbonate and ethylenediamine are evenly mixed to obtain a mixed solid-liquid; an ethanol solution of hexachlorocyclotriphosphazene is added dropwise to the mixed solid-liquid at 5-10°C, and after the addition is completed, the temperature is raised to 20°C, and the reaction is continued for 2-3 hours to obtain a reaction liquid; the reaction liquid is heated to 80-90°C, the solvent is removed by reaction, and a solid is obtained; the solid is washed with deionized water and vacuum dried to obtain a solid intermediate A; S3, mixing TAIC and solid intermediate A, and then adding polylactic acid to blend to obtain a blend; adding the blend to a torque rheometer, blending at 190-200° C. for 5-10 minutes to obtain flame-retardant polylactic acid.
2. The method for preparing a degradable modified PS plastic bowl according to claim 1, characterized in that: In step S1, the usage ratio of hexachlorocyclotriphosphazene and ethanol is 35-45 g:200 mL; in step S2, the usage ratio of anhydrous potassium carbonate and ethylenediamine is 10 g:35-50 mL; in step S2, the vacuum drying temperature is 70-80° C. and the vacuum drying time is 30-60 min.
3. The method for preparing a degradable modified PS plastic bowl according to claim 1, characterized in that: In step S3, the usage ratio of TAIC, intermediate A and polylactic acid is 5-10g:30-40g:200-300g; the mixing speed is 100r / min, and the mixing time is 5min; the blending speed is 100r / min, and the blending time is 5-10min.
4. The method for preparing a degradable modified PS plastic bowl according to claim 1, characterized in that: The preparation method of PS-phenyl maleic anhydride copolymer comprises the following steps: Polystyrene, phenyl maleic anhydride and DMF are mixed evenly, and then an initiator BPO is added, and the temperature is raised to 120-140°C, and the reaction is carried out for 3 hours to obtain a mixed solid-liquid; the mixed solid-liquid is then heated to 155-160°C, and the DMF solvent is distilled off to obtain a solid; the solid is washed with deionized water and then vacuum dried to obtain a PS-phenyl maleic anhydride copolymer.
5. The method for preparing a degradable modified PS plastic bowl according to claim 4, characterized in that: The usage ratio of polystyrene, phenyl maleic anhydride, DMF and initiator BPO is 8-10g:10-15g:100mL:0.3g; the vacuum drying temperature is 70-80°C, and the vacuum drying time is 30min.
6. The method for preparing a degradable modified PS plastic bowl according to claim 1, characterized in that: The degradable polyurethane is prepared by the following steps: A1. Mix sorbitol and polyol vegetable oil, raise the temperature to 80-100° C., then add toluene diisocyanate, stir to obtain a mixed solid-liquid; add a catalyst to the mixed solid-liquid, and react at a constant temperature of 80° C. for 3-5 hours to obtain a polymer; A2. Add 10-20 g of a small molecule chain extender to the polymer, stir at a constant temperature of 50-60° C. for 10-20 min to obtain a sample; cast the sample in a polytetrafluoroethylene mold, and cure at 70° C. for 5-7 days to obtain a degradable polyurethane.
7. The method for preparing a degradable modified PS plastic bowl according to claim 6, characterized in that: In step A1, the polyol vegetable oil is any one of castor oil, soybean oil or palm oil and a combination thereof, and the catalyst is dibutyltin dilaurate; the dosage ratio of sorbitol, polyol vegetable oil, toluene diisocyanate and catalyst is 18g:5g:80g:0.3-0.5g; the stirring speed is 5-10min and the stirring time is 100r / min; in step A2, the small molecule chain extender is any one of ethylene glycol, 1,3-butanediol, 1,4-butanediol or 1,6-propylene glycol and a combination thereof.
8. The method for preparing a degradable modified PS plastic bowl according to claim 1, characterized in that: The temperature of melt blending is 180-200°C, the rotation speed is 50r / min, the melt blending time is 10-20min; the molding time is 8-10min, the molding pressure is 10MPa; the pressure holding cooling time is 10min.
9. A degradable modified PS plastic bowl, characterized in that: The degradable modified PS plastic bowl is prepared by the method for preparing a degradable modified PS plastic bowl as described in any one of claims 1 to 8.
Citation Information
Patent Citations
Composite reclaimed PS / ABS / PP (polystyrene / acrylonitrile butadiene styrene / polypropylene) crosslinked modified flame-retardant plastic and preparation method thereof
CN105255094A